Analisis Liabilitas dan Ekuitas terhadap Laba Operasional pada PT AlloBank Indonesia, Tbk - Talitha Afrah Rafania; Nura Anggraeny; Kinanti Dara Putri; Azzahra Verdi; Syti Sarah M (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This research was conducted with the aim of analyzing whether the Liability and Equity factors affect Operational Profit at PT.Allo Bank Indonesia. In this analysis, using a quantitative approach which uses secondary data collected from the quarterly financial reports of PT. AlloBank Indonesia, Tbk. from 2015 to 2022. The data was analyzed using descriptive analysis techniques, multiple linear regression analysis, classical assumption tests, and hypothesis testing. The results of the study show that partially Liabilities do not have a significant effect while Equity has a positive relationship and has a significant effect on Operating Income. Taken together, the Liability and Equity Variables have a significant impact on operating profit with an adjusted R square of 10.3%. However, this study has limitations on the representativeness of the secondary data which will affect the results of the analysis so that for future researchers, it is advisable to use more complete data and consider the measurement of relevant additional variables.